2019
DOI: 10.1136/heartjnl-2018-313511
|View full text |Cite
|
Sign up to set email alerts
|

Clinical trials of transcatheter aortic valve replacement

Abstract: Transcatheter aortic valve replacement(TAVR) has emerged as an effective treatment option in patients with severe aortic stenosis, in large part due to a robust evidence base generated by a series of randomised controlled trials (RCTs). During the past decade more than 15 000 patients have been randomised worldwide in nine clinical trials, mostly for regulatory approval in the USA, making it one of the most carefully scrutinised medical devices at the time of introduction into clinical practice. Initial trials… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…58 Taking these aspects into account, life-threatening or major bleeding rates have been reported to be between 2.4% and 41.7% at 30 days and between 3.2% and 46.1% at 1-year follow-up. [2][3][4][5][6][7][8]21 Notably, regardless of the aetiology, both acute and late bleeding are associated with poor clinical outcomes and increased mortality rate. 9,10,12 In addition, bleeds may be augmented by coexisting conditions, such as older age, frailty, fall risk, renal failure, liver disease, malignancy, anaemia and coagulation disorders, as well as by AF and antithrombotic therapy.…”
Section: Bleeding Eventsmentioning
confidence: 99%
See 1 more Smart Citation
“…58 Taking these aspects into account, life-threatening or major bleeding rates have been reported to be between 2.4% and 41.7% at 30 days and between 3.2% and 46.1% at 1-year follow-up. [2][3][4][5][6][7][8]21 Notably, regardless of the aetiology, both acute and late bleeding are associated with poor clinical outcomes and increased mortality rate. 9,10,12 In addition, bleeds may be augmented by coexisting conditions, such as older age, frailty, fall risk, renal failure, liver disease, malignancy, anaemia and coagulation disorders, as well as by AF and antithrombotic therapy.…”
Section: Bleeding Eventsmentioning
confidence: 99%
“…Across TAVI landmark studies, the 30-day stroke incidence ranges between 0.6% and 6.7%, increasing to 1.2-10.6% at 1 year. [2][3][4][5][6][7][8]21 The mechanism underpinning CVEs following TAVI is multifactorial. It includes valve-related flow turbulence, vessel wall disruption, metallic frame exposure (which in turn induces platelet activation) and patientrelated prothrombotic factors, irrespective of the valve type (balloonor self-expandable) or procedural approach (transfemoral or transapical).…”
mentioning
confidence: 99%
“… 2 A vast majority of clinical trials has failed to stop the progression of AVS, 3 and for that reason, the only available therapeutic treatment relies on aortic valve prosthesis implantation. 4 …”
mentioning
confidence: 99%
“…Randomized controlled trials have shown noninferiority of transcatheter AVR over surgical AVR in medium-and low-risk patients with severe aortic stenosis. 1 Thus, a number of patients with severe aortic stenosis will undergo transcatheter AVR. Nevertheless, surgical AVR still remains the gold standard treatment for aortic valve disease, as surgical bioprostheses have shown excellent hemodynamic performance with high freedom from structural valve degeneration and reoperation at very long-term follow-up.…”
mentioning
confidence: 99%